2020
DOI: 10.1186/s13643-020-01289-7
|View full text |Cite
|
Sign up to set email alerts
|

Under-five anemia and its associated factors with dietary diversity, food security, stunted, and deworming in Ethiopia: systematic review and meta-analysis

Abstract: Background Anemia is the most common hematologic disorder of children in the globe. There are fragmented and inconclusive study findings on under-five anemia in Ethiopia. Understanding the distribution of anemia is an important step for program planners and policymakers. Therefore, this systematic review was aimed to assess the pooled prevalence of anemia and associated factors with dietary diversity, food security, stunted, and deworming in Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 35 publications
5
40
0
2
Order By: Relevance
“…Interestingly, we found association between serum ferritin and HAZ-score (Table 2) and it was supported by our results that showed iron deficient children had two times risks to be stunted (Table 3). This finding was consistent with a systematic review in Ethiopia that pointed out poor dietary diversity, stunting, food insecurity, and not dewormed were predictors of anemic under-five children [25]. Food insecurity has consequences in both macro and micronutrient deficiencies that increased the risk of child anemia [26].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, we found association between serum ferritin and HAZ-score (Table 2) and it was supported by our results that showed iron deficient children had two times risks to be stunted (Table 3). This finding was consistent with a systematic review in Ethiopia that pointed out poor dietary diversity, stunting, food insecurity, and not dewormed were predictors of anemic under-five children [25]. Food insecurity has consequences in both macro and micronutrient deficiencies that increased the risk of child anemia [26].…”
Section: Discussionsupporting
confidence: 88%
“…The finding of previous literature revealed that different factors are associated with anemia among children. These include: maternal age [ 18 ], twin births [ 19 ], birth order [ 20 ], residence [ 21 ], child age [ 22 , 23 ], place of delivery [ 24 , 25 ], deworming [ 26 ], childhood nutritional status [ 27 ], household wealth status [ 18 ], maternal education [ 28 ], infectious diseases (malaria, hookworm) [ 29 ], and maternal anemia [ 30 , 31 ]. Besides, in developing countries, anemia varies by socioeconomic factors [ 17 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also excluded children with no haemoglobin values registered and those categorized as wasted (moderate and severe acute malnutrition, weight‐for‐height Z score <−2 standard deviations). We decided to exclude acutely malnourished children because this condition is commonly associated with other diseases that could acutely modify haemoglobin values, such as dehydration caused by diarrheal diseases (Belachew & Tewabe, 2020; Díez & Marrodán, 2018; Leidman et al, 2018; Thakur, Chandra, Pemde, & Singh, 2014). In the case of women having more than one eligible child aged 6 to 59 months, we considered data from their eldest child in order to avoid duplicate observations for the same mother.…”
Section: Methodsmentioning
confidence: 99%
“…Deficiencies iron, folic acid and hydroxocobalamin are known to be common causes of anaemia (Janus & Moerschel, 2010). Chronic malnutrition and anaemia share many risk factors and children at risk of stunting is also at risk of anaemia and vice versa (Anticona & San‐Sebastian, 2014; Belachew & Tewabe, 2020; Hussien, Larijani, & Esmaillzadeh, 2019; Rahman, Mushfiquee, Shahed, & Howlader, 2019; Reinhardt & Fanzo, 2014).…”
Section: Introductionmentioning
confidence: 99%